2022
DOI: 10.58283/fs.v1i2.67
|View full text |Cite
|
Sign up to set email alerts
|

Percepción de los estudiantes universitarios colombianos sobre la asignatura de Metodología de la Investigación

Abstract: El presente artículo tiene como objetivo explorar la percepción provista por los universitarios colombianos frente a la asignatura Metodología de Investigación. Para el desarrollo de este trabajo se optó por un diseño cuantitativo de carácter descriptivo. Se localizaron los comentarios de 500 estudiantes universitarios adscritos a 10 grupos de Facebook utilizando operadores de búsqueda y ajustando temporalmente el periodo de publicación (2019-2022), después se sistematizaron en una matriz externa para la revis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Recent qualitative research with Colombian university students revealed that they regarded RM as an annoying, unimportant, and easy-to-pass course. The study also identified the teacher's pedagogical practice and the curricular content of the course as the reasons for the negative perceptions (Álvarez Merlano et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recent qualitative research with Colombian university students revealed that they regarded RM as an annoying, unimportant, and easy-to-pass course. The study also identified the teacher's pedagogical practice and the curricular content of the course as the reasons for the negative perceptions (Álvarez Merlano et al, 2022).…”
Section: Introductionmentioning
confidence: 99%